Tesco Stores (M) Sdn. Bhd.: Employee Retention Strategy To Reduce Cashier Turnover Rate - Teh, Peh Nee (2014)
This case study examined the high turnover rate among cashiers at Tesco grocery stores in Bukit Mertajam, Malaysia. The main objective of the study was to identify the issues and the root causes of high employee turnover. This study interviewed key informants such as the HR manager and the trading manager in the Front-end department and reviewed company reports to get some ideas about the current situation. All interviews were conducted in Tesco stores located in Bukit Mertajam during office working hours. The case using five analytical tools including Cause-and-Effect Analysis (Fishbone Diagram); Observation and Effect Analysis; SWOT analysis, Benchmarking Analysis, and a cashier‟s satisfaction survey.